Social enterprise interventions to tackle food insecurity in Sub-Saharan Africa: a scoping literature review - von Salmuth, Victoria; Phillips, Thomas; Bhattacharjee, Anindita; Kwansa, Albert; Akparibo, Robert (Frontiers in Public Health, 2025)
BackgroundFood insecurity remains a significant global challenge, particularly in low- and middle-income countries (LMICs), where it contributes to the growing prevalence of the double burden of malnutrition. Social enterprises (SEs) are increasingly recognized as effective tools for addressing social challenges through innovative and sustainable approaches. However, their role in mitigating food insecurity in Sub-Saharan Africa has not been extensively explored. This scoping review seeks to assess the scope, depth, and impact of existing research on SE interventions aimed at addressing food insecurity in Sub-Saharan Africa.MethodsWe conducted searches across six academic databases, Medline, EMBASE, CINAHL, Scopus, Web of Science, and Google Scholar, to identify peer-reviewed studies evaluating social enterprise (SE) interventions addressing food insecurity in Sub-Saharan Africa. Additional relevant studies were identified by reviewing citations and references from the initial search results. The selected literature was screened, and data were extracted by two independent reviewers. To ensure accuracy, a third reviewer verified the data extraction process.ResultsOverall, 10 articles were included in this review. The identified SE interventions were categorized into three groups: (1) livestock production and supply, (2) microcredit and loan ventures, and (3) biodiversity and education programs.ConclusionSocial enterprises encompass a promising way forward in contributing to tackle food insecurity in SSA. SEs often work in cooperation with other organizations such as community support groups, Non-Governmental Organizations (NGOs), and governmental organizations. The sustainability of such interventions depends on financial viability, local ownership, adaptability, integration with local systems, and effective monitoring and evaluation.